2011
DOI: 10.1039/c0dt01598a
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) complexes of N2O and N3O donor ligands as functional models for catechol dioxygenase enzymes: ether oxygen coordination tunes the regioselectivity and reactivity

Abstract: A series of mononuclear iron(III) complexes of the type [Fe(L)Cl(3)], where L is a systematically modified N(2)O or N(3)O ligand with a methoxyethyl/tetrahydrofuryl ether oxygen donor atom, have been isolated and studied as models for catechol dioxygenases. The X-ray crystal structures of [Fe(L2)Cl(3)] 2, [Fe(L6)Cl(3)] 6, [Fe(L5)(TCC)Cl] 5a, where H(2)TCC = tetrachlorocatechol, [Fe(L6)(TCC)Br] 6a, and the μ-oxo dimer [{Fe(L6)Cl}(2)O](ClO(4))(2) 6b have been successfully determined. In [Fe(L2)Cl(3)] 2 the N(2)O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 84 publications
4
8
0
Order By: Relevance
“…1.936 Å) than those to the nitrogen atoms (av. 2.016 Å), which are in agreement with the literature values . The bond angles O(1)‐Fe(1)‐N(1), O(2)‐Fe(1)‐N(2) and O(3)‐Fe(1)‐O(4) are all close to 180° [170.298, 166.709 and 173.339°, respectively].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…1.936 Å) than those to the nitrogen atoms (av. 2.016 Å), which are in agreement with the literature values . The bond angles O(1)‐Fe(1)‐N(1), O(2)‐Fe(1)‐N(2) and O(3)‐Fe(1)‐O(4) are all close to 180° [170.298, 166.709 and 173.339°, respectively].…”
Section: Resultssupporting
confidence: 89%
“…2.304(2) Å]. Comparable Fe‐Cl bond lengths have been found in similar octahedral iron(III) complexes reported in the literature …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Complexes with L62 or L65 gave a higher percentage of the extradiol products, while for the complex with L63, more intradiol products were formed. The obtained results indicate that the oxygen of the ether group significantly accelerates the reaction [64].…”
Section: Tridentate Ligandsmentioning
confidence: 73%
“…However, the comparison showed that the complexes with tripodal L62-L65 ligands gave the reaction rates more than 10 times higher. The presence of substituents in the ligand rings, their nature, and steric effects significantly affect the acidity of iron (III), which influenced the selectivity of the cleavage reaction [64].…”
Section: Tridentate Ligandsmentioning
confidence: 99%